(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The article interprets the presence and implications of myths in the Hindi movie Astitva with an archetypal perspective. In Astitva, we see a woman, despite all her steadfastness in her love and duties, being banished from her husband’s heart due to her chance sexual encounter with her music instructor once. Before passing value judgments on her predicament, it needs to be comprehended beyond particular contexts and codes. Mythological templates help us in doing that and in making us be empathetically convinced as well.In the wake of mythology and cinema’s presence everywhere around us in the form of names, brands, literary allusions, and the psychological influence they have on people to make their characters their role models, this study takes up the two to explore the possibility of their working hand in hand, in addition to their old association of one just offering the ‘material’ to the other to work upon. The pedagogical or the psychological function of mythology, as propounded by Joseph Campbell, serves as the yard stick to analyse the mythical aspect of the chosen movie.